2018
DOI: 10.1039/c8sc03677b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of styrene aziridination by iron(iv) nitrides

Abstract: A combined experimental and computational investigation reveals that styrene aziridination by an iron(iv) nitride occurs by a stepwise mechanism involving multistate character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…This means that differences in reactivity are likely caused by steric rather than electronic effects. Indeed, while [PhB­( Mes Im) 3 Fe IV N] engages in partial electrophilic nitrogen transfer reactions to phosphines, isocyanides, and olefins, 1 exhibits complete chemical inertness with respect to its reactivity with triphenyl phosphine, trimethyl phosphine, tert -butyl isocyanide, and cyclooctene, as evidenced by 1 H NMR spectroscopy (Supporting Information Figures S18–S22). Comparison of the respective solid-state and geometry-optimized structures lead us to argue that this might be due to the tight blocking of reaction trajectories other than the axial one in 1 by the mesityl substituents, which is not the case in [PhB­( Mes Im) 3 Fe IV N].…”
Section: Results and Discussionmentioning
confidence: 99%
“…This means that differences in reactivity are likely caused by steric rather than electronic effects. Indeed, while [PhB­( Mes Im) 3 Fe IV N] engages in partial electrophilic nitrogen transfer reactions to phosphines, isocyanides, and olefins, 1 exhibits complete chemical inertness with respect to its reactivity with triphenyl phosphine, trimethyl phosphine, tert -butyl isocyanide, and cyclooctene, as evidenced by 1 H NMR spectroscopy (Supporting Information Figures S18–S22). Comparison of the respective solid-state and geometry-optimized structures lead us to argue that this might be due to the tight blocking of reaction trajectories other than the axial one in 1 by the mesityl substituents, which is not the case in [PhB­( Mes Im) 3 Fe IV N].…”
Section: Results and Discussionmentioning
confidence: 99%
“…Finally, a recent study of olefin aziridination using a Fe IV -nitride catalyst revealed that the reaction is governed by an inverse electronic effect with a nucleophilic active species. 49 To try and understand these disparate behaviors, we decided to turn our attention to a purely nitrogen-based ligand system and study the mechanism of styrene aziridination by the N 6 -ligated iron complex (N4Py)Fe IV (NTs) 2+ species (Scheme 1). 1 IV =NTs 2+ has so far been the most thoroughly studied Fe-imido complex.…”
Section: Introductionmentioning
confidence: 99%
“…Iron‐nitrido species [3] are nitrogen analogues of iron‐oxo species and have been proposed as key intermediates in a number of industrial [4] and biomimetic [5] nitrogen fixation processes where ammonia can be formed via multiple proton/electron transfer steps onto molecular or surface‐bound Fe‐nitrido moieties. In the literature, reactivity studies of terminal Fe‐nitrido complexes with organic substrates [6] including phosphines, [6a,f,g,l] isocyanides, [6e,l] and alkenes [6c,h,i,k,m] are mostly studied for trigonal Fe‐nitrido complexes [6a,d,l, 7] having high Fe‐N nitrido bond order according to the molecular orbital (MO) diagram (Figure 1 a). [3e, 6a, 7c] On the other hand, Fe‐nitrido complexes in tetragonal symmetry [6c, 8] are generally less stable due to population of Fe d electron(s) in antibonding dπ* orbital(s) [3e, 9] .…”
Section: Introductionmentioning
confidence: 99%